Extrahepatic factors in hepatic immune regulation - Zhang, Shaoying; Lu, Shemin; Li, Zongfang (Frontiers in Immunology, 2022)
The liver is a site of complex immune activity. The hepatic immune system tolerates harmless immunogenic loads in homeostasis status, shelters liver function, while maintaining vigilance against possible infectious agents or tissue damage and providing immune surveillance at the same time. Activation of the hepatic immunity is initiated by a diverse repertoire of hepatic resident immune cells as well as non-hematopoietic cells, which can sense “danger signals” and trigger robust immune response. Factors that mediate the regulation of hepatic immunity are elicited not only in liver, but also in other organs, given the dual blood supply of the liver via both portal vein blood and arterial blood. Emerging evidence indicates that inter-organ crosstalk between the liver and other organs such as spleen, gut, lung, adipose tissue, and brain is involved in the pathogenesis of liver diseases. In this review, we present the features of hepatic immune regulation, with particular attention to the correlation with factors from extrahepatic organ. We describe the mechanisms by which other organs establish an immune association with the liver and then modulate the hepatic immune response. We discuss their roles and distinct mechanisms in liver homeostasis and pathological conditions from the cellular and molecular perspective, highlighting their potential for liver disease intervention. Moreover, we review the available animal models and methods for revealing the regulatory mechanisms of these extrahepatic factors. With the increasing understanding of the mechanisms by which extrahepatic factors regulate liver immunity, we believe that this will provide promising targets for liver disease therapy.